A Review Paper On Vision Based Identification, Detection And Tracking Of Weld Seams Path In Welding Robot Environment - Hairol Nizam, Mohd Shah; Marizan, Sulaiman; Ahmad Zaki, Shukor; Muhammad Herman, Jamaluddin; Mohd Zamzuri, Ab Rashid (Canadian Center of Science and Education, 2016)
Welding is an important technology especially for joining between two metals, fabricated and repairing metals products in manufacturing industries such as in automotive industries. To increase the productivity and lower cost, today the welding operation in industries introduces the welding robot. The main challenges to using welding robot is time taken to program robot path for a new job in low to medium volume manufacturing industries. This paper begins with the review of identified, detected and tracked the weld seams path with different type of welding in welding environment. Next, a review of analysis an identified and detect the weld seams path approaches is included with advantages, drawback and limitation. This paper is concluded by a comprehensive summary which discussed the disadvantages and limitation of a robust approach in each stage. The improvement of a new approach in each stage depends on the lack, limitation and the results which are expected from the work.